AGRARIAN HISTORY OF UZBEKISTAN DURING THE SOVIET PERIOD - Sattarov Akram Madaminovich. (Scholar Express Journal, 2024)
This article analyses the agrarian policy of the Soviet state in the period after. The article notes that during the leadership of Stalin, serious mistakes were made in policy towards agriculture. Not enough importance was attached to the development of agriculture, the material and technical base of the collective farms remained in serious condition. In the material situation of collective farmers and the general rural population, significant positive changes did not occur
Keywords: Agrarian policy; agriculture